Beyond Equal Rights: Equality of Opportunity in Political Participation - Paul Hufe; Andreas Peichl (Center for Economic Studies and ifo Institute (CESifo), 2018)
While it is well documented that political participation is stratified by socio-economic characteristics, it is an open question how this finding bears on the evaluation of the democratic process with respect to its fairness. In this paper we draw on the analytical tools developed in the equality of opportunity literature to answer this question. We investigate to what extent differential political participation is determined by factors that lie beyond individual control (circumstances) rather than being the result of individual effort. Using rich panel data from the US, we indeed find a lack of political opportunity for the most disadvantaged circumstance types. Opportunity shortages tend to complement each other across different forms of participation and persist over time. Family characteristics and psychological conditions during childhood emanate as the strongest determinants of political opportunities.
Keywords: D39; D63; D72; 330; equality of opportunity; political participation